Interaction between norovirus and Histo-Blood Group Antigens: A key to understanding virus transmission and inactivation through treatments?. (December 2020) - Chassaing, M.; Boudaud, N.; Belliot, G.; Estienney, M.; Majou, D.; de Rougemont, A.; Gantzer, C.
Abstract: Human noroviruses (HuNoVs) are a main cause of acute gastroenteritis worldwide. They are frequently involved in foodborne and waterborne outbreaks. Environmental transmission of the virus depends on two main factors: the ability of viral particles to remain infectious and their adhesion capacity onto different surfaces. Until recently, adhesion of viral particles to food matrices was mainly investigated by considering non-specific interactions (e.g. electrostatic, hydrophobic) and there was only limited information about infectious HuNoVs because of the absence of a reliable in vitro HuNoV cultivation system. Many HuNoV strains have now been described as having specific binding interactions with human Histo-Blood Group Antigens (HBGAs) and non-HBGA ligands found in food and the environment. Relevant approaches to the in vitro replication of HuNoVs were also proposed recently. On the basis of the available literature data, this review discusses the opportunities to use this new knowledge to obtain a better understanding of HuNoV transmission to human populations and better evaluate the hazard posed by HuNoVs in foodstuffs and the environment. Highlights: HBGA-binding to HuNoVs is specific and highly diverse. HBGA-binding may select HuNoVs with native capsid. HBGA-binding seems not be a proof of HuNoV infectivity. HBGA-like-binding in food matrices may play a role in HuNoV transmission but results need to be clarified.